Tropical agriculture in Algeria 1840-1940 Cotton and Indigo as a model - Bourakna, Ali; Dehane, Slimane; Benmouiza, Brahim (The International tax journal, 2025)
The French Agricultural project in Algeria formed a major base of settlement and economic hegemony from the beginning. It founded this strategy by sending the tropical agriculture project to produce many crops such as: Tobacco, cotton, indigo, coffee, aromatic plants, and hashish, in line with the expectations of the French market, which has lost contact with the region of the Far East and the Pacific Islands. In light of these circumstances, France decided to establish this agriculture in Algeria. This research grapples to answer the following questions: What are the rules that I bet on, and what is the nature of this project and its economic background?